The Use of a Dynamic Programming Approach in Inventory Control of Clove in the Production of Cigarette: A Case Study at PT. Gandum, Malang. - Hidayat, Arif; Mustaniroh, Siti Asmaul (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
The research aim was to plan a monthly optimum level of clove used for cigarette production in the period from September 2003 to August 2004 and to estimate its total inventory cost, employing a dynamic programming approach. The research was divided into two stages. The first one was analysis to forecast a monthly clove used and then followed by an inventory analysis using a dynamic programming approach. The calculation was based on predetermined costs on clove i.e. Rp 45,000/kg (a purchasing cost), Rp 38,800/order (an ordering cost) and Rp 47/kg of a holding cost. The backward recursive equation for the dynamic programming approach was expressed as: fj(Xj) = 45000(Xj) + 38800 + 47(Xj+Sj-1-Dj) + fj-1(Xj-1), with the following constraints: Xj + Sj-1 ≤ G, Xj + Sj-1 ≥ Dj and Xj ≥ 0. An optimization using a dynamic programming approach showed that total inventory cost during the planned period was Rp 435,415,516,791 with an ending inventory of 3,058 kg of clove. It was found that the use of such an approach for PT.Gandum eventually reduced the total inventory cost of clove by Rp 514,577,099. The sensitivity analysis also indicated that the model was still valid for the monthly clove need up to 1,600 kg. Key words: inventory control, dynamic programming, cigarette production